Imaging the migrating border cell cluster in living Drosophila egg chambers. - Tekotte, H; Tollervey, D; Davis, I (2007)
Cell migration is a key process in animal development and central to the spread of cancer. Border cell migration in Drosophila egg chambers is an excellent general model for cell migration, but lacks techniques for studying this process in living cells. Here, we describe a simple and effective method of preparing egg chambers in halocarbon oil. The movement and behavior of the migrating border cells can reproducibly be followed in up to 25 egg chambers simultaneously by time-lapse microscopy using a variety of green fluorescent protein markers on a widefield microscope over a period of 4 hr. Our studies reveal a remarkably linear migration route of the border cell cluster and highly dynamic activity within their cluster. Migrating cells rapidly alter their relative positions and generate transient protrusions. These activities are likely to play key roles in the mechanism of migration and cannot readily be analyzed using fixed samples.